2016
DOI: 10.1007/s00384-016-2641-3
|View full text |Cite
|
Sign up to set email alerts
|

The important risk factor for lateral pelvic lymph node metastasis of lower rectal cancer is node-positive status on magnetic resonance imaging: study of the Lymph Node Committee of Japanese Society for Cancer of the Colon and Rectum

Abstract: An LPLN-positive status with a short axis ≥5 mm on MRI is an important predictor of LPLN metastasis, but PRLN status is not a strong predictor of PRLN metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…A previous study identified the risk factors for LLNM as female sex, lower rectal cancer location, lymphatic invasion, venous invasion, wall progression, and paraintestinal lymph node metastasis ≥ 5 mm in width on magnetic resonance imaging [ 35 ]. Another group found that the diagnostic ability for LLNM is more promising at a short axis of 5 mm than it is at 10 mm [ 36 ]. However, there are reports of pathological lymph node metastases being found in approximately half of the lymph nodes that were judged to be small (< 5 mm) on diagnostic imaging [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study identified the risk factors for LLNM as female sex, lower rectal cancer location, lymphatic invasion, venous invasion, wall progression, and paraintestinal lymph node metastasis ≥ 5 mm in width on magnetic resonance imaging [ 35 ]. Another group found that the diagnostic ability for LLNM is more promising at a short axis of 5 mm than it is at 10 mm [ 36 ]. However, there are reports of pathological lymph node metastases being found in approximately half of the lymph nodes that were judged to be small (< 5 mm) on diagnostic imaging [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several risk factors for positive lateral lymph nodes have been reported previously. Preoperative risk factors include age, sex, tumor location, depth of invasion, central nodal involvement, and lateral node size [13][14][15][16][17][18][19][20][21][22][23]. Studies on the size of lymph nodes in terms of the major or minor axis and various lengths have been conducted; however, in this study, lateral lymph nodes with minor axes shorter than 7.0 mm, as identified using CT and magnetic resonance imaging, constituted the criterion for negative metastasis, and many institutions in Japan now use this criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported that the assessment of LNs in CRC by any imaging modality is difficult because LN size alone is not a consistent diagnostic criterion of metastatic involvement. 9,34 Other studies have demonstrated that although ADC values may be valuable to identify metastatic LNs, it is often problematic to discriminate between metastatic and nonmetastatic LNs on the basis of ADC values alone because of the considerable overlap between the ADC values of metastatic and nonmetastatic LNs. [35][36][37][38] Based on the ability to predict microstructural complexity, QSI may be a useful tool for noninvasive evaluation of the extent of LNM in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…QSI was also useful to discriminate between metastatic and nonmetastatic LNs in CRC. Prior studies have reported that the assessment of LNs in CRC by any imaging modality is difficult because LN size alone is not a consistent diagnostic criterion of metastatic involvement . Other studies have demonstrated that although ADC values may be valuable to identify metastatic LNs, it is often problematic to discriminate between metastatic and nonmetastatic LNs on the basis of ADC values alone because of the considerable overlap between the ADC values of metastatic and nonmetastatic LNs .…”
Section: Discussionmentioning
confidence: 99%